2001
DOI: 10.1063/1.1380247
|View full text |Cite
|
Sign up to set email alerts
|

Ionic and electronic dark decay of holograms in LiNbO3:Fe crystals

Abstract: The lifetimes of nonfixed holograms in LiNbO 3 :Fe crystals with doping levels of 0.05, 0.138, and 0.25 wt % Fe 2 O 3 have been measured in the temperature range from 30 to 180°C. The time constants of the dark decay of holograms stored in crystals with doping levels of 0.05 and 0.25 wt % Fe 2 O 3 obey an Arrhenius-type dependence on absolute temperature T, but yield two activation energies: 1.0 and 0.28 eV, respectively. For these crystals, two different dark decay mechanisms are prevailing, one of which is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
4

Relationship

6
3

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Several attempts to solve the problem are reported in literature [136,137,138,139]. Among them the most common technique for LiNbO 3 , the material in question, is called thermal fixing [136,140,141,142,143,144]. The underlying idea is as follows: As discussed in section 3.2, holographically recording a grating means, that a light-induced space-charge density of electrons modulates the refractive index via the electrooptic effect.…”
Section: Thermal Fixing In Hydrated and Dehydrated Linbo 3 :Fementioning
confidence: 99%
“…Several attempts to solve the problem are reported in literature [136,137,138,139]. Among them the most common technique for LiNbO 3 , the material in question, is called thermal fixing [136,140,141,142,143,144]. The underlying idea is as follows: As discussed in section 3.2, holographically recording a grating means, that a light-induced space-charge density of electrons modulates the refractive index via the electrooptic effect.…”
Section: Thermal Fixing In Hydrated and Dehydrated Linbo 3 :Fementioning
confidence: 99%
“…For LiNbO 3 :Fe crystals, the highest practical doping level is approximately 0.06 wt.% Fe 2 O 3 and is limited by dark decay. [12][13][14] It also has been found that by using Mn instead of Fe as a dopant, the practical highest doping level can be increased considerably to obtain a larger M͞# and greater sensitivity. 15 Another way to improve the M͞# and sensitivity for the LiNbO 3 -based holographic storage system is to use transmission geometry instead of the 90-degree geometry.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In general both, proton compensation and electron tunneling, contribute to the dark decay in LiNbO 3 crystals. In crystals with low doping levels, proton compensation dominates the dark decay, and the time constant of this type of dark decay is inversely proportional to the proton concentration.…”
Section: Introductionmentioning
confidence: 99%
“…8 For example, in the widely used LiNbO 3 :Fe crystals, the highest practical doping level is ϳ0.1 wt.% Fe 2 O 3 and is found to be limited by a fast dark decay. [8][9][10][11] It is desired to have highly doped crystals with acceptable dark decay.…”
Section: Introductionmentioning
confidence: 99%